The Erasmus Corner: place-making of a sanitised nightlife spot in the Bairro Alto (Lisbon, Portugal) - Malet Calvo, D.; Nofre, J.; Nofre, J.; Geraldes, M. (Leisure Studies, 2017)
Nightlife economic activity has emerged as a key strategy in the regeneration of historical quarters. The case of the Bairro Alto district (Lisbon) exhibits a more gradual and distinct development caused by the marginal and transgressive practices of nightlife visitors, who have resisted its gentrification for decades. Some areas in the Bairro Alto (specially the upper side) have maintained their dangerous character and marginalisation for several years, even after the 2008 urban reform programme. It is only recently, with the growing presence of Erasmus students in Bairro Alto, that the upper side has finally become safe and sanitised through leisure activities. In this article, the interplay of several social actors (foreign students, municipal authorities, night-time entrepreneurs and Erasmus organisers) explains the process of place-making regarding the new Erasmus Corner. The spatial colonisation of this spot has accelerated social cleansing of the upper side of the neighbourhood, concluding the district’s night-time pacification.